2019
DOI: 10.31580/apss.v3i2.508
|View full text |Cite
|
Sign up to set email alerts
|

Case Study of Workplace Spirituality on Organizational Commitments among University Members in Malaysia

Abstract: Based on the recent past studies (Ahmad & Omar, 2015; Ke & Deng, 2018; Ghani, Abdullah & Allah, 2018), there are an increasing attention from the researchers to examine the workplace spirituality in the organization. This research study seeked to study the influences of workplace spirituality (Allen & Meyer , 2000) on organizational commitments among university members in Malaysia. Data of 240 responses were collected and analyzed via partial least square structural equation modelling to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…In addition, Kazemipour's et al's (2012) study on nurses found an impact of affective commitment on performance outcomes. Consistent with few prior studies on spirituality and commitment (Chelliah et al, 2018) and based on the person-organization fit theory (Edwards, 2007), which is often used to explain the compatibility between a person's characteristics and organizational features, we suggest that spirituality at work positively affects employees' organizational commitment. When health-care professionals practice spirituality, they feel more immersed and satisfied in an organization that fosters spirituality, which then may facilitate and increase their commitment toward the organization.…”
Section: Indirect Relationship Between Spiritual Expression and Organ...supporting
confidence: 86%
See 1 more Smart Citation
“…In addition, Kazemipour's et al's (2012) study on nurses found an impact of affective commitment on performance outcomes. Consistent with few prior studies on spirituality and commitment (Chelliah et al, 2018) and based on the person-organization fit theory (Edwards, 2007), which is often used to explain the compatibility between a person's characteristics and organizational features, we suggest that spirituality at work positively affects employees' organizational commitment. When health-care professionals practice spirituality, they feel more immersed and satisfied in an organization that fosters spirituality, which then may facilitate and increase their commitment toward the organization.…”
Section: Indirect Relationship Between Spiritual Expression and Organ...supporting
confidence: 86%
“…Various studies have shown positive effects of spirituality at work on commitment (Saadatyar et al , 2020). For instance, Chelliah et al (2018) found evidence that workplace spirituality is linked to affective, normative and continuance commitment, while Campbell and Hwa (2014) only found positive effects on two forms of commitment – namely affective and normative – while continuance commitment was negatively related to commitment (Campbell and Hwa, 2014; Rego and Pina E Cunha, 2008). In addition, Kazemipour’s et al ’s (2012) study on nurses found an impact of affective commitment on performance outcomes.…”
Section: Spiritual Expression At Workmentioning
confidence: 99%
“…Chelliah et al (2018) underline that workplace spirituality is significantly correlated with all three dimensions of organizational commitment, but with a different correlation strength. The empirical work of Campbell and Hwa (2014) shows that workplace spirituality, through the alignment between personal and organizational values, the sense of enjoyment and the feeling of contribution to community, has a positive effect on affective and normative commitments.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 91%
“…Normative and affective commitment have been found to generate loyalty in organization, in a way that that performances that draw upon these dimensions have a deeper and "thicker" characteristic that reinforces long term organizational health (Campbell and Hwa, 2014). Chelliah et al (2018) underline that workplace spirituality is significantly correlated with all three dimensions of organizational commitment, but with a different correlation strength. The empirical work of Campbell and Hwa (2014) shows that workplace spirituality, through the alignment between personal and organizational values, the sense of enjoyment and the feeling of contribution to community, has a positive effect on affective and normative commitments.…”
Section: The Role Of Organizational Commitmentmentioning
confidence: 99%
“…Workplace spirituality has four foremost effects on standard workplace dimensions: performance (Daniel, 2010; Pirkola et al ., 2016), behavior, commitment and satisfaction (Fanggida et al ., 2016). This suggests that performance of organizations, teams and individuals is positively associated with workplace spirituality; organizational citizenship behavior is positively associated with workplace spirituality and employee performance and acts as a mediator between them; perceptions of organizational spirituality are positively linked with the affective and normative commitment of individuals and organizational commitment (Chelliah et al ., 2019); workplace spirituality is positively associated with job and team satisfaction . The theories, variables, elements and effects of workplace spirituality are presented in Table 1 .…”
Section: Spiritual Self-managed Teamsmentioning
confidence: 99%